A narrative study of newly graduated registered Swedish nurses' establishment in the profession and the portrayal of a healthcare organisation. Issue 4 (28th June 2019) - Blomberg, Helena; Welander, Jonas
Abstract : Purpose: The purpose of this paper is to investigate how the participants talk about their experiences as newly graduated nurses, managers and nursing colleagues in the context of "newcomers' establishment in the profession" and to identify how they portray the healthcare organisation in their narratives. Design/methodology/approach: A narrative approach is used to reveal and illustrate three perspectives on the topic "new-comers' establishment". In total, 14 interviews are conducted with 4 managers, 4 nursing colleagues and 6 newly graduated registered nurses. The focus of this study is how a healthcare organisation embraces and retains newly graduated registered nurses and how this is perceived. Findings: The newcomers' establishment is facilitated by an orientation programme and an orientation period, individual support provided by managers and colleagues, and the creation of trust to boost confidence in nursing situations. The organisation is portrayed as struggling with high workloads, nursing shortages, high levels of responsibility and showing concern and an interest in the newcomer. The parties criticise the university for not teaching the most basic knowledge, thereby revealing the existence of a theory-practice gap. Originality/value: The research shows how building trust amongst the organisation's members is essential for creating a satisfying workplace and the retention of newly graduated registered nurses. Empirical descriptions of newly graduated nurses, managers and nursing colleagues experiences of "newcomers establishment" are rare, which is why the description of such "establishment" in this research increases the value of the paper.